Genotoxicity of cigarette smoking in maternal and newborn lymphocytes - Carvalho de Assis, Katia Regina; Placido Ladeira, Marcelo Sady [UNESP]; Bueno, Roberta C. A. [UNESP]; dos Santos, Bruna F. [UNESP]; Dalben, Ivete [UNESP]; Salvadori, Daisy Maria Favero [UNESP] (Elsevier B.V., 2009)
Tobacco smoke contains a large number of substances known to induce DNA damage and to be hazardous to human health. Several reviews and meta-analyses have reported an association between maternal or paternal smoking habits and genetic-related diseases, such as cancer, in children. The aim of the present study was to evaluate the level of DNA damage in lymphocytes of active- and passive-smoking mothers and in their newborns, using the comet assay. A total of 40 active smokers, 40 passive smokers. and 40 non-smokers, and their respective newborns, were evaluated. The active smokers presented a statistically significant increase of DNA damage when compared to the non-smokers and passive-smokers. No significant difference was observed between passive and non-smoking women. Similar results were detected in newborns. Those born to active-smoking mothers presented higher levels of DNA damage than those from passive- and non-smoking mothers. Additionally, no significant difference was detected between newborns from non-smoking and passive-smoking mothers. Also, no statistically significant difference in DNA damage was observed between mothers and their respective newborns, and a positive correlation in the level of DNA damage was detected between them. Logistic regression analyses showed positive associations between DNA damage, spontaneous abortion and smoking status. In conclusion, our data indicate that tobacco exposure during pregnancy has genotoxic effects for both mother and child, and it can be considered an important risk factor for childhood cancer or other genetic-related diseases. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Cigarette smoke; DNA damage; Genotoxicity; Passive smoking; Pregnant smoking women